Effect of Surface and Hageman Factor on the Endogenous or Spontaneous Activation of the Fibrinolytic System - Iatridis, Sotirios G.; Ferguson, John H. (Thrombosis and Haemostasis, 1961)
The effect of wettable surfaces and Hageman factor on the activation of the fibrinolytic system was investigated.The fibrinolytic activity was estimated mainly by the euglobulin lysis test. Experiments were carried out with Normal and Hageman-deficient plasmas.The euglobulin lysis time of both plasmas was greatly affected by varying the surface exposure. Normal euglobulin suspension incubated at 37° C, and tested at intervals, showed an increase of fibrinolytic activity. The evidence suggests that this activity is related to the generation of endogenous activator. The rate of generation was a function of surface. Hageman-deficient euglobulin suspension, under the same conditions, did not generate endogenous activator.Evidence is presented to show that Hageman factor is different from proactivator and plasminogen.It is concluded that wettable surfaces and Hageman factor may have a role in the endogenous (or spontaneous) activation of the fibrinolytic system.